2019
DOI: 10.3857/roj.2019.00220
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of neutrophil-to-lymphocyte ratio in locally advanced non-small cell lung cancer treated with concurrent chemoradiotherapy

Abstract: Purpose: This study aimed to investigate neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) as prognostic factors in patients with locally advanced non-small cell lung cancer (NSCLC) who received concurrent chemoradiotherapy (CCRT). Materials and Methods: We retrospectively analyzed 66 patients with locally advanced NSCLC treated with definitive CCRT. Among these patients, 95% received paclitaxel/carboplatin or docetaxel/cisplatin. The median radiation dose was 66 Gy in 33 fractions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Furthermore, reports suggest subcategorization of white blood cells or platelets and their functions associated with tumor progression or suppression 6 8 . Numerous studies have confirmed the clinical significance of the neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), and platelet-to-lymphocyte ratio (PLR) in HCC 9 12 . Additionally, our group has also reported the prognostic significance of NLR, LMR, and PLR in newly diagnosed previously untreated patients with HCC using a large single institutional cohort data and validated the results in the same cohort registered at different times 13 .…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, reports suggest subcategorization of white blood cells or platelets and their functions associated with tumor progression or suppression 6 8 . Numerous studies have confirmed the clinical significance of the neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), and platelet-to-lymphocyte ratio (PLR) in HCC 9 12 . Additionally, our group has also reported the prognostic significance of NLR, LMR, and PLR in newly diagnosed previously untreated patients with HCC using a large single institutional cohort data and validated the results in the same cohort registered at different times 13 .…”
Section: Introductionmentioning
confidence: 96%
“…Since most of the studies usually lean on surgery and/or chemotherapy as treatment modalities, we focused our attention in the literature on the studies on patients who were subjected to radiotherapy, as our aim is to make a comparison with the results of our study. All series had a retrospective design and included patients with locally advanced NSCLC treated with curative radiotherapy 1,23–28 . The inferences obtained can be listed as follows: First, these indices were often examined individually in published studies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, some researchers evaluated post treatment values and changes regarding these indices. While the change of indices remained prognostic, pre‐treatment values of indices unexpectedly did not show a survival advantage 24 . Third, the studies examined the prognostic effects of indices on OS and PFS.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent chemoradiotherapy may dynamically alter PD-L1 expression and numbers of CD8 + tumour infiltrating lymphocytes [98,99]. Pre-therapeutic blood-based parameters, or their change during chemoradiotherapy, may predict prognosis [100][101][102].…”
Section: Integration Of Immunotherapy In Radiochemotherapy In Locally...mentioning
confidence: 99%